SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPS SISWA KELAS lV SEKOLAH DASAR - Yulinda; Syahira; Wiky Santia Witama; Wulandari; Susi Ratna Sari; Zahra Maharani Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of the Discovery Learning model on the learning outcomes of fourth-grade elementary school students through the Systematic Literature Review (SLR) method. This study is motivated by the low level of active student participation in the social studies learning process, so a learning model that can improve student understanding and learning outcomes is needed. The method used in this study is a Systematic Literature Review by collecting and analyzing scientific articles relevant to the research topic. Data were obtained through the Google Scholar database using the Publish or Perish application with the keywords "Discovery Learning", "learning outcomes", and "social studies". Based on the search results, 15 SINTA-indexed national journal articles were obtained that match the research focus. Data analysis techniques were carried out by identifying, classifying, and evaluating research results related to the application of the Discovery Learning model in social studies learning in elementary schools. The results of the study indicate that the Discovery Learning model is effective in improving the learning outcomes of fourth-grade elementary school students. The application of this model is able to increase student activeness, conceptual understanding, critical thinking skills, and collaborative skills in the learning process. In addition, students become more active in finding and concluding learning materials independently. Thus, the Discovery Learning model can be used as an effective alternative learning strategy to create active, meaningful, and student-centered social studies learning in elementary schools.